Food values: How they relate to legality - Marchini, Andrea; Polenzani, Bianca; Ceccarelli, Giulia; Mariano, Eleonora; Martino, Gaetano (Frontiers in Sustainable Food Systems, 2023)
A value is an implicit principle that arises from judgements about everything around people, whereas a value system is a set of values ordered according to personal preferences. In this context, values can be seen as the adherence to an implicit or explicit set of rules, many of which are related to legality. In this study, legality is understood as the willingness of citizens to abide by the existing set of formal laws. A value system can guide consumers' food choices and provide information on their preferences. In this way, the citizens' food value system can influence the decisions of producers and policymakers. The present study investigates the food value system of a sample of young adults using the Best-Worst Scale method. Values such as environmental impact rank high in their value system, indicating that adherence to a set of implicit rules and regulations concerning the environment are very important values when choosing food.